CONDITIONS AND PROBLEMS OF FORMATION OF PROFESSIONALLY SIGNIFICANT QUALITIES IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE MANAGERS OF FOREIGN ECONOMIC ACTIVITY - Liliya Khomyak (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
Conditions and problems of the formation of рrofessionally significant qualities in the process of professional training of future managers of foreign economic activity are determined in the following article. For this purpose certain patterns in the formation of рrofessionally significant qualities in the process of professional training of future managers of foreign economic activity in such countries as Germany, France, Great Britain, the USA in comparison to the Ukrainian pattern have been analysed and observed. In the course of research work common and different traits in studying system, curriculum, credit division, subject teaching in Ukrainian and foreign system of education have been defined. Peculiarities of professional training of foreign specialists and the set of competences of future managers have been specified. In conclusion, faults and problems of the Ukrainian system, steps to their solutions and changes through the positive charachteristics of professional training and quality of education in foreign universities have been determined.